1985
DOI: 10.1148/radiology.157.2.4048458
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder MR imaging. Part II. Neoplasm.

Abstract: The potential of magnetic resonance (MR) imaging for the evaluation and staging of bladder tumors was analyzed in 15 patients (11 cases of transitional cell carcinoma, two adenocarcinomas, one leiomyosarcoma, and one leiomyoma). Neoplasms were characterized by size, site, and growth pattern, and the accuracy of the staging was compared with the results of computed tomography and pathologic study. Malignancies were accurately detected and staged by MR imaging in 12 of 14 patients (85%). Tumor site and degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…Also, TUUS has limitations in differentiating tumour stages because acoustic shadows are produced by tumour surface calci®cation or ultrasound is absorbed by large tumours. Conventional MRI is ineffective for bladder tumour staging, being unable to separate not only T1 from T2a, but also T2a from T2b [1,16]. Pavone et al [17] compared the clinical staging accuracy of these three imaging methods and concluded that TUUS was better than the other two methods for local staging.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TUUS has limitations in differentiating tumour stages because acoustic shadows are produced by tumour surface calci®cation or ultrasound is absorbed by large tumours. Conventional MRI is ineffective for bladder tumour staging, being unable to separate not only T1 from T2a, but also T2a from T2b [1,16]. Pavone et al [17] compared the clinical staging accuracy of these three imaging methods and concluded that TUUS was better than the other two methods for local staging.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were performed with low field-strength scanners (0.5 Tesla) and contained a small sample size [22,24,28]. In addition, Buy et al reported a staging accuracy of 60% for non-enhanced MR images [23], and in this study under-staging (at a rate of 33%) was the most common error.…”
Section: Initial Results For Bladder Tumor Stagingmentioning
confidence: 68%
“…In addition, a lesion extending into the perivesical fat (T3) or the adjacent organs (T4) is also diagnosed as MIBC [22][23][24].…”
Section: Staging Criteria On Mrmentioning
confidence: 99%
“…[11][12][13][14] A lesion at the base of the tumor with intact muscle layer of low SI was considered stage T1 or lower and with focally disrupted muscle layer of low SI without perivesical infiltration, stage T2. A lesion extending into the perivesical fat was considered T3 and extending into adjacent organs, T4.…”
Section: T Staging On T 2 Wimentioning
confidence: 99%